Predatory Stink Bug, Alcaeorrhynchus grandis (Dallas): EENY165/IN322, 10/2000 - Richman, David B.; Mead, Frank W. (EDIS, 2003)
Alcaeorrhynchus grandis (Dallas) is a very large (20 mm) predatory stink bug which occurs in several row crops and preys on other insects, especially lepidopterous larvae. The stages in the life cycle have never been illustrated and are presented here so that they can be identified in the field. This document is EENY-165 (originally published as DPI Entomology Circular 192), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 2000. EENY165/IN322: Predatory Stink Bug, Alcaeorrhynchus grandis (Dallas) (Hemiptera: Pentatomidae) (ufl.edu)